Surgery with and without extracorporeal circulation in patients aged above 65 and kidney injury assessed by NGAL concentration - Kowalczuk-Wieteska, Anetta; Szewczyk, Marta; Lindon, Sandra; Zembala, Marian (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: Human neutrophil gelatinase-associated lipocalin (NGAL) is one of the most sensitive predictive indices of acute kidney injury (AKI). Aim : The aim of the work was to determine whether NGAL is a sensitive predictive index of AKI in elderly patients (> 65 years old) undergoing cardiac surgery, with and without extracorporeal circulation. Material and methods: The study group encompassed 30 patients aged > 65 years, treated surgically, 18 with extracorporeal circulation (group I) and 12 without (group II). The serum concentrations of NGAL, cystatin C and the serum glomerular filtration rate (GFR) were assessed 24 h before surgery, and then 2 h and 24 h after surgery. The tests were carried out using immunochemical, nephelometric and standard clinical biochemical methods. Results : In both groups, pre-operative cardiac, pulmonary and renal functions were normal. Hypertension was successfully treated in 16 patients, diabetes type 2 with normal baseline NGAL and no signs of nephropathy in 4 patients. In group I, the pre-operative levels of NGAL, cystatin C and GFR were normal. Two hours after surgery, there was a statistically significant increase in the level of NGAL, whilst GFR and cystatin C remained unchanged. Twenty-four hours after surgery, NGAL decreased slightly but was still statistically significantly higher than the baseline value. In group II, by contrast, there were no significant differences between pre- and post-operative levels of NGAL, cystatin C and GFR. Conclusions: Neutrophil gelatinase-associated lipocalin is the most sensitive biomarker of transient renal ischemia related to the use of extracorporeal circulation in elderly patients with normal pre- and post-operative renal function. In elderly patients with normal renal function before and after cardiac surgery without extracorporeal circulation, NGAL levels are normal.